KAJIAN TERHADAP PUTUSAN MAHKAMAH AGUNG No. 653 K/Pid/2011 TENTANG TINDAK PIDANA PENCURIAN - Bambang Ali Kusumo (Universitas Slamet Riyadi, 2012)
Abstract:Decision of the Supreme Court No. 653 K/Pid/2011 less oriented to justice but moreoriented towards legal certainty. It can be seen from the decision that is based on thesubstance of justice, but only based on a majority vote of the judges. The existence ofthis decision be one that affects the issuance of Perma No. 02 Tahun 2012 on theadjustment limits the number of minor criminal offenses and penalties in the KUHP.Key words: Keadilan, Kemanfaatan dan Kepastian Hukum.